2022
DOI: 10.3390/biomedicines10081995
|View full text |Cite
|
Sign up to set email alerts
|

GRP78, a Novel Host Factor for SARS-CoV-2: The Emerging Roles in COVID-19 Related to Metabolic Risk Factors

Abstract: The outbreak of coronavirus disease 19 (COVID-19), caused by the infection of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has resulted in an unprecedented amount of infection cases and deaths, leading to the global health crisis. Despite many research efforts, our understanding of COVID-19 remains elusive. Recent studies have suggested that cell surface glucose-regulated protein 78 (GRP78) acts as a host co-receptor for SARS-CoV-2 infection and is related to COVID-19 risks, such as older age,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 97 publications
0
9
0
Order By: Relevance
“…Next, we analyzed the level of expression of known SARS-CoV2 receptors and co-receptors in the hCOs. RNA sequencing of late stage (6M) hCOs confirmed low expression of the major SARS-CoV2 receptor, ACE2 2,16,17 , and higher expression of some of the SARS-CoV2 coreceptors such as NRP1, CD147/BSG; GRP78/HSPA5; DPP4 and AXL 7,16,[18][19][20][21][22][23][24][25][26] as well as some of the enzymes involved in the cleavage of the SARS-CoV2 virus spike protein to mediate viral entry to the cell, such as transmembrane serine protease 2 (TMPRSS2), cathepsin B (CTSB), cathepsin L (CTSL) and furin 14,23 (Fig. 1M).…”
Section: Sars-cov2 Virus Consistently Infects Human Cortical Organoid...mentioning
confidence: 99%
See 1 more Smart Citation
“…Next, we analyzed the level of expression of known SARS-CoV2 receptors and co-receptors in the hCOs. RNA sequencing of late stage (6M) hCOs confirmed low expression of the major SARS-CoV2 receptor, ACE2 2,16,17 , and higher expression of some of the SARS-CoV2 coreceptors such as NRP1, CD147/BSG; GRP78/HSPA5; DPP4 and AXL 7,16,[18][19][20][21][22][23][24][25][26] as well as some of the enzymes involved in the cleavage of the SARS-CoV2 virus spike protein to mediate viral entry to the cell, such as transmembrane serine protease 2 (TMPRSS2), cathepsin B (CTSB), cathepsin L (CTSL) and furin 14,23 (Fig. 1M).…”
Section: Sars-cov2 Virus Consistently Infects Human Cortical Organoid...mentioning
confidence: 99%
“…However, the expression of ACE2 co-receptors that potentiate SARS-CoV2 infectivity has been reported in a number of tissues including the brain. These co-receptors include neuropilin 1 (NRP1) cell surface receptor 16,1820 , dypeptidylpeptidase 4 (DPP4) 21 , tyrosine-protein kinase receptor UFO (AXL) 22 , the transmembrane glycoprotein (CD147/BSG) 7,23,24 , stress-inducible ER chaperone (GRP78/HSPA5) 25,26 . These reports support the possibility that alternative receptors and co-receptors are mediating SARS-CoV2 entry in brain cells.…”
Section: Introductionmentioning
confidence: 99%
“…Specific receptors within the immune system, including Neuropilin-1 (NRP1), C-lectin type receptors (CLR) such as mannose receptor (MR), dendritic cellspecific intracellular adhesion molecule-3-grabbing non-integrin (DC-SIGN), homologous dendritic cell-specific intercellular adhesion molecule-3-grabbing non-integrin-related (L-SIGN), and macrophage galactose-type lectin (MGL), along with Toll-like receptors (TLRs) including TLR1, TLR4, and TLR6, have been identified as receptors in SARS-CoV-2 [43]. Additionally, non-immune receptors such as the glucose regulated protein 78 (GRP78) have been implicated in the viral process [44]. Moreover, Ezrin and Dipeptidyl peptidase-4 (DPP4) have been suggested as potential targets against SARS-CoV-2, although their roles remain unconfirmed [45].…”
Section: Sars-cov-2 Receptorsmentioning
confidence: 99%
“…A different clinical study, involving a significant number of participants, demonstrated that COVID-19 patients exhibited GRP78 levels approximately five times greater than those observed in the healthy control group Recent research has demonstrated that in addition to the receptor ACE2, csGRP78 can function as a co-receptor for the SARS-CoV-2 spike protein. In order to enter target cells more easily, csGRP78 forms a protein complex on the cell surface with the host cell receptor ACE2 and directly interacts with the SARSCoV-2 spike protein (Shahriari-Felordi et al 2022 ; Sabirli et al 2021 ; Shin et al 2021 , 2022a ; Carlos et al 2021 ; Shin et al 2022a , b ) 17 Ovarian Cancer Cell survival, angiogenesis, chemoresistance GRP78 enhances cell survival, promotes angiogenesis, and contributes to resistance to chemotherapy in ovarian cancer. GRP78 enhances cell survival by activating pro-survival signaling pathways, such as the PI3K/AKT pathway.…”
Section: Introductionmentioning
confidence: 99%